Negociando com a incerteza: proposição de um framework guiado pelo design para projetação de artefatos que promovam a criação de conhecimento no contexto das cidades - Stoffel, Hiparcio Rafael (Universidade do Vale do Rio dos Sinos, 2022)
The growing urban concentration has challenged cities to deal with social problems of greater uncertainty and complexity, but the efforts used to solve them have not been satisfied from a traditional approach. Every city is a carrier of knowledge, creative and intelligent to some extent, varying according to its culture, values, beliefs and abilities. The exercise of creativity, entrepreneurship and innovation are determining factors in dealing with situations of high uncertainty and creating knowledge. This research, based on the concepts of Research Through Design, studied the creation of knowledge in the treatment of complex problems and situations in cities from the construction of artifacts, in order to mediate the understanding of the problem, identify opportunities and create knowledge under the Strategic Design perspective. Having metaprojectual thinking as one of its foundations, strategic design takes a look at the design movement as a reflexive, conversion and generative process. The methodological approach used included exploratory, empirical and qualitative research and its application in a design group formed by specialist designers and diffuse designers. The analysis of design processes was explored using the linkography method. As a result, a framework structured in six perspectives was proposed to support the process of Designing Artifacts for the Creation of Knowledge: (a) Engagement and Interaction, (b) Context and Understanding, (c) Externalization of Ideas, (d) Format, (e) Application and (f) Joker.
Keywords: Design estratégico; Criação de conhecimento; Problemas complexos; Research through design; Linkografia; Cidades criativas e inteligentes; Strategic design; Knowledge creation; Wicked problems; Linkography; Creative and smart cities; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial